2020
DOI: 10.1186/s12884-020-2843-0
|View full text |Cite
|
Sign up to set email alerts
|

Online mindfulness-based intervention for women with pregnancy distress: design of a randomized controlled trial

Abstract: Background Psychological distress during pregnancy is common: up to 20% of the childbearing women experience symptoms of depression and anxiety. Apart from the adverse effects on the woman herself, pregnancy distress can negatively affect pregnancy outcomes, infant health, postpartum mother-child interaction and child development. Therefore, the development of interventions that reduce pregnancy distress is very important. Mindfulness-based interventions (MBIs) show promising positive effects o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 47 publications
4
16
0
Order By: Relevance
“…Such a promising benefit may be that a single intervention programme that incorporates the predictors together could potentially mitigate psychological distress and promote healthy functioning in the study population. Quantitative findings thus aligned with related studies that have demonstrated that these predictors are imperative for reducing psychological distress (Brion et al, 2014;Deko et al, 2016;Hulsbosch et al, 2020;Ristriyani et al, 2018). Further, the quantitative findings are a theoretical consensus with the social mentality theory of self-compassion, meaning in life theory, and relational frame theory that guided this study (Frankl, 1976;Gilbert, 2017;Hayes et al, 2001;Hermanto & Zuroff, 2016).…”
Section: Discussion and Implications For Clinical Practicesupporting
confidence: 82%
See 2 more Smart Citations
“…Such a promising benefit may be that a single intervention programme that incorporates the predictors together could potentially mitigate psychological distress and promote healthy functioning in the study population. Quantitative findings thus aligned with related studies that have demonstrated that these predictors are imperative for reducing psychological distress (Brion et al, 2014;Deko et al, 2016;Hulsbosch et al, 2020;Ristriyani et al, 2018). Further, the quantitative findings are a theoretical consensus with the social mentality theory of self-compassion, meaning in life theory, and relational frame theory that guided this study (Frankl, 1976;Gilbert, 2017;Hayes et al, 2001;Hermanto & Zuroff, 2016).…”
Section: Discussion and Implications For Clinical Practicesupporting
confidence: 82%
“…An additional novelty of the current study is that the study was among the first to demonstrate the important predictive impact of a single model comprising self-compassion, meaning in life, and acceptance of illness; on psychological distress in PLWHAs. This is supportive of the absence of this single model in the literature (Deko et al, 2016;Hulsbosch et al, 2020;Ogueji & Okoloba, 2020).…”
Section: Discussion and Implications For Clinical Practicesupporting
confidence: 80%
See 1 more Smart Citation
“…A study conducted in China that targeted pregnant women with mild or moderate symptoms of depression and anxiety found that an Internet-based mindfulness intervention improved depression and anxiety (Yang et al 2019 ), while a UK-based study did not find a significant benefit of a Web-based intervention, mainly due to high attrition rates (22 out of 107 in intervention arm completed the study) (Krusche et al 2018 ). There are also a few other studies using Web-based mindfulness interventions that are currently underway, though the results are not yet available (Cohen and Dimidjian 2018 ; Hulsbosch et al 2020 ). The present study differs from these studies because we used a self-paced, mobile-based intervention that does not require logging into sessions at specified time.…”
Section: Discussionmentioning
confidence: 99%
“…However, the related literature for the pregnant population is sparse. Reported studies have been preliminary [ 26 - 29 ], aimed only at the postpartum period [ 30 ], treated mindfulness as a single component of a complex integrated intervention [ 31 ], or used only a pre-post test design [ 32 ]. Nevertheless, some pilot studies have supported online MBI as a promising technique to help expectant mothers reduce depressive symptoms [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%